Ask Me for a Blessing (You Know You Need One) - Dannhauser, Adrian (1517 Media, 2022)
Once a week Adrian Dannhauser stands outside her church with a sign that reads ""Ask me for a blessing."" What is a blessing? Do you have to believe to receive one? Dannhauser offers glimpses into the tender, holy, and funny moments she has with people looking for a blessing and delves into the power that ancient ideas hold in a disenchanted world.